Pengaruh In-Store Display, Bonus Pack, dan Sales Person Terhadap Impulse Buying Dengan Emotional Response Sebagai Variabel Intervening Studi Pada Konsumen Alfamart Cabang Kotalama Malang - Amailia Savira; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe Research amis tosee the effect of in-store displays, bonus pack and sales person against the impuls buying with the emotional response as an intervening variable. The population of this study is all of the konsumer alfamart kotalama branchto a total of 4,500. Sampling is take nusing the accidental sampling with a total sample of 100. Research is using a path analysis model. In this Research shows that in-store displays, bonus pack, and sales person have a direct bearing on impuls buying. In-store displays, bonus pack, and sales person person directly affect the emotional response. Emotiona l respons directly affects impuls buying. In-store displays, bonus pack, and sales person influence is not directly against impuls buying through emotional response.Keyword : In-storeDisplay, Bonus Pack, Sales Person, Emotional Response, Impulse Buying